2019
DOI: 10.3847/1538-3881/ab2390
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble of Bayesian Neural Networks for Exoplanetary Atmospheric Retrieval

Abstract: Machine learning (ML) is now used in many areas of astrophysics, from detecting exoplanets in Kepler transit signals to removing telescope systematics. Recent work demonstrated the potential of using ML algorithms for atmospheric retrieval by implementing a random forest (RF) to perform retrievals in seconds that are consistent with the traditional, computationally expensive nested-sampling retrieval method. We expand upon their approach by presenting a new ML model, plan-net, based on an ensemble of Bayesian … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 26 publications
0
68
0
1
Order By: Relevance
“…In contrast, the BNN posterior sits in the middle of the degenerate peaks, and remains tightly constrained around the offset value. It is worth noting that this implementation of the BNN is not equivalent to the one used in Cobb et al (2019), as they use a different form of the likelihood which has not been tested on such high-resolution data. Cobb et al (2019) In Cobb et al (2019), it was suggested that the random forest in Márquez-Neila et al (2018) has the potential to produce over-confident, incorrect posteriors based on a mock retrieval from a test dataset.…”
Section: Comparison To Other Machine-learning Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the BNN posterior sits in the middle of the degenerate peaks, and remains tightly constrained around the offset value. It is worth noting that this implementation of the BNN is not equivalent to the one used in Cobb et al (2019), as they use a different form of the likelihood which has not been tested on such high-resolution data. Cobb et al (2019) In Cobb et al (2019), it was suggested that the random forest in Márquez-Neila et al (2018) has the potential to produce over-confident, incorrect posteriors based on a mock retrieval from a test dataset.…”
Section: Comparison To Other Machine-learning Techniquesmentioning
confidence: 99%
“…It is worth noting that this implementation of the BNN is not equivalent to the one used in Cobb et al (2019), as they use a different form of the likelihood which has not been tested on such high-resolution data. Cobb et al (2019) In Cobb et al (2019), it was suggested that the random forest in Márquez-Neila et al (2018) has the potential to produce over-confident, incorrect posteriors based on a mock retrieval from a test dataset. This forest was trained on WFC3 spectra with 13 data points and predicted 5 parameterstemperature, free chemical abundances of H 2 O, HCN and NH 3 , and a grey cloud opacity, κ 0 .…”
Section: Comparison To Other Machine-learning Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we introduce our algorithm for generating informed priors in the context of transmission spectroscopy of exoplanetary atmospheres. This is an area which has already seen some application of machine learning, for example through the use of neural networks (Cobb et al 2019) or supervised machine learning algorithms (Márquez-Neila et al 2018). These methods generally look to the machine learning algorithm to do the full retrieval of atmospheric parameters from data.…”
Section: Why Unsupervised Machine Learning?mentioning
confidence: 99%
“…On the neural network front, utilized a Generative Adversarial Network (GAN), a DL network architecture that can generate the closest synthetic spectrum and its associated atmospheric properties for a given observed spectrum. Cobb et al (2019) developed a Bayesian Neural Network to model the posterior distribution between atmospheric parameters. To speed up the computationally expensive radiative transfer simulation process, Himes et al (2020) trained an ML surrogate forward model and demonstrated its potential to significantly reduce retrieval time.…”
Section: Introductionmentioning
confidence: 99%